Seminar Inspiratif: Para Guru Diajak Menjadi Pendidik Hebat Di Era Revolusi Industri 4.0 - Non Syafriafdi; Muhammad Azky; Rizky Fadhilah; Rangga Hafizh Darmawan; Khairifo Khairifo; Putri Anggraini Suci Ramadani; Fina Putri; Marisa Marisa; Hanny Olivya; Natasha Widy Pratiwi; Lastika Br Silalahi (FKIP, Universitas Palangka Raya, 2023)
The Inspirational Seminar